Effect of Polysaccharide Conformation on Ultrafiltration Separation Performance. (15th May 2021) - Eder, Severin; Zueblin, Patrick; Diener, Michael; Peydayesh, Mohammad; Boulos, Samy; Mezzenga, Raffaele; Nyström, Laura
Graphical abstract: Highlights: Conformation and narrow dispersity during degradation of scleroglucan Mw maintained. Rejection yield of randomly coiled pullulan and rigid rod-like scleroglucan differed. Effect of conformation on yield and molecular weight distribution in retentate. Conformation and membrane material proved decisive for ultrafiltration. Large deviations between actual and nominal MWCO reported. Abstract: The manifold array of saccharide linkages leads to a great variety of polysaccharide architectures, comprising three conformations in aqueous solution: compact sphere, random coil, and rigid rod. This conformational variation limits the suitability of the commonly applied molecular weight cut-off (MWCO) as selection criteria for polysaccharide ultrafiltration membranes, as it is based on globular marker proteins with narrow Mw and hydrodynamic volume relation. Here we show the effect of conformation on ultrafiltration performance using randomly coiled pullulan and rigid rod-like scleroglucan as model polysaccharides for membrane rejection and molecular weight distribution. Ultrafiltration with a 10 kDa polyethersulfone membrane yielded significant different recoveries for pullulan and scleroglucan showing 1% and 71%, respectively. We found deviations greater than 77-fold between nominal MWCO and apparent Mw of pullulan and scleroglucan, while recovering over 90% polysaccharide with unchanged Mw . We anticipate our work as starting point towards an optimized membrane selection for polysaccharide applications.